Respuesta :

Answer:

f-1(x) = √x. +5

Step-by-step explanation:

f(x) = (x-5)^2

x = (y-5)²

√x = y-5

√x +5 = y

The inverse of the given function is required.

The inverse is [tex]g(x)=5+\sqrt{x}[/tex]

The function is

[tex]f(x)=(x-5)^2[/tex] for [tex]x\geq 5[/tex]

Isolating [tex]x[/tex]

[tex]y=(x-5)^2\\\Rightarrow \pm\sqrt{y}=x-5\\\Rightarrow x=5+\sqrt{y},5-\sqrt{y}[/tex]

Now [tex]x\geq 5[/tex]

Since, [tex]x[/tex] is not imaginary [tex]y\nless 0[/tex].

Now, [tex]5-\sqrt{y}[/tex] will not be a solution as the value of [tex]x[/tex] will become less than [tex]5[/tex] for any positive [tex]y[/tex].

Hence, the inverse is [tex]g(x)=5+\sqrt{x}[/tex]

Learn more:

https://brainly.com/question/14899241